Separasi dan Reattachment Aliran di Belakang Gundukan (Bump) Setengah Lingkaran, Segitiga dan Persegi Panjang - Setyo Hariyadi S.P.; Setiyo Setiyo; Supriadi Supriadi (Jurnal Penelitian)
Characteristic of viscous flow through a contour always become the interesting topic to be studied. This research studied characteristic of turbulent viscous flow through a flat plate mounted by bump. Target of this research is to know the flow characteristic through the semicircle, triangle and quadrangular bump, and also to get distribution coefficient of pressure (Cp), separation point, coefficient of pressure drag (CDp) and coefficient of total drag (CD). Beside that, in this research also conduct smoke visualization to know visualization of turbulent viscous flow through a flat plate mounted by bump. This experiment is conducted in subsonic wind tunnel. Form of the bump that is used are semicircle, triangle and quadrangular, and free stream velocity equal to 9.75 m/s and 15.5 m/s. Pressure coefficient got from static pressure measurement over flat plate and bump by using wall pressure tap. Coefficient of pressure drag (CDp) got from calculation based pressure. The measurement of velocity profile over flat plate and bump by using pitot tube. Measurement conducted at 6 point before side of upstream bump, 1 point at top bump and 13 point after side of downstream bump where distance between the points are 20 mm. While for the direction of vertical, the measurement taken at 80 point started from height 80 mm from surface until near the surface. Existence of bump on flat plate result the flow becomes separation so that generate the total drag force addition over flat plate. The highest total drag force occured on flat plate with triangle bump, then on flat plate with quadrangular bump and the smallest occur on flat plate with semicircle bump.